2007
DOI: 10.1038/sj.bjc.6603987
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant intensive chemoradiotherapy induction in non-metastatic inflammatory breast cancer: long-term follow-up

Abstract: The aim of this study was to evaluate with a long follow-up the efficacy of concomitant chemoradiotherapy in non-metastatic inflammatory breast cancer (IBC) and to evaluate the breast conservation rate. Between 1990 and 2000, 66 non-metastatic patients with IBC were treated with chemotherapy and concomitant irradiation. The induction chemotherapy consisted of epirubicine, cyclophosphamide and vindesine, in association with split-course bi-fractionated irradiation to a total dose of 65 Gy with concomitant cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…However, despite combined modality treatment, IBC continues to have a very poor prognosis and further efforts are required to improve systemic control to eradicate occult microscopic disease by incorporating the use of anthracycline-based chemotherapy (10,30), taxanes (36), high-dose chemotherapy (23,35,37,38), and new agents (39)(40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite combined modality treatment, IBC continues to have a very poor prognosis and further efforts are required to improve systemic control to eradicate occult microscopic disease by incorporating the use of anthracycline-based chemotherapy (10,30), taxanes (36), high-dose chemotherapy (23,35,37,38), and new agents (39)(40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…The publications originated from 20 countries: Korea (six studies), [8][9][10][11][12][13] Japan (five studies), [14][15][16][17][18] Brazil (four studies), 3,[19][20][21] Canada (three studies), [22][23][24] United States (three studies), [25][26][27] Italy (three studies), [28][29][30] Switzerland (three studies), [31][32][33] France (two studies), 34,35 China (one study), 36 Singapore and Sweden (one study, study performed in both countries), 37 Scotland (one study), 38 Spain (one study), 39 Finland (one study), 40 India (one study), 41 England (two studies), 42,45 Mexico (one study), 43 Poland (one study), 44 and the Netherlands (one study). 46 From the aim established for this study, the variables to be investigated were defined: the study design, study site/country, number of subjects, age of the subjects, five year survival rate, disease-free five year survival rate, factors that contribute to the increase in survival rates.…”
Section: Methodsmentioning
confidence: 99%
“…12 Other studies have reported 2-, 10-, and 20-year overall survival rates of 82%, 32%-38%, and 19%, respectively using various regimens. [13][14][15][16] Although radiotherapy retreatment is common across many types of cancer, median time between retreatment episodes has been observed to be longest in breast cancer (12.5 months). 17 As our patient was treated several years prior with radiotherapy for DCIS, the need for repeat radiotherapy adds complexity to her care.…”
Section: Discussionmentioning
confidence: 99%